A novel method for preparing the antibacterial glass fibre mat using laser treatment. Issue 2 (14th February 2014) - Wiener, Jakub; Shahidi, Sheila; Goba, Makabongwe Mkhululi; Šašková, Jana
Abstract : In this study, CO2 laser treatment was used as a novel method for creating antibacterial properties on glass mat. Different metallic salts such as CuO, ZnO and AgNO3 were even applied on surface of glass fiber mat, then irradiated with the laser light beam (100  μ s). Metal particles were deposited on the surface of samples, and the antibacterial has been developed, through incorporation of metal particles on glass mats. The antibacterial properties of the fabrics were connected with the presence of metal particles on their surface. The amounts of metal particles on the surface were compared using X-ray fluorescence (XRF) and energy dispersive X-ray spectrometer (EDS). Also the morphological properties of the fabrics were observed using a scanning electron microscope (SEM). The experimental work suggests that the change in properties induced by laser can effect an improvement in certain textile products.